Association between blood essential metal elements in early pregnancy and gestational diabetes mellitus - Chen, Guozhen; Wu, Li; Ji, Cunwei; Xia, Jianhong; Liu, Guocheng (Frontiers in Nutrition, 2025)
ObjectivesThe purpose was to assess the levels of iron (Fe), magnesium (Mg), copper (Cu), calcium (Ca), zinc (Zn) in the blood of pregnant women during early pregnancy, and to evaluate their potential association with gestational diabetes mellitus (GDM).MethodsWe enrolled 9,112 pregnant women who underwent testing for essential metal elements at Guangdong Women and Children Hospital during the first trimester in 2015–2022. The basic information of pregnant women and peripheral blood samples were collected, and five essential metal elements in whole blood were detected by atomic absorption spectrometry. The relationship between these essential metal elements and GDM was analyzed using the generalized linear regression model (GLM), weighted quantile sum regression (WQS), quantile g-computation regression (QGC), and Bayesian kernel machine regression (BKMR).ResultsAnalysis of the correlation between essential metal elements and GDM revealed significant associations. Compared with the first quantile concentration level, the fourth quantile level of Fe (OR = 1.347, 95%CI: 1.158 ~ 1.568), Zn (OR = 1.379, 95%CI: 1.185 ~ 1.606) and Mg (OR = 1.192, 95%CI: 1.022 ~ 1.392) exhibited significant associations with GDM. Restricted cubic spline (RCS) analysis showed a positive linear relationship between Fe, Zn, and Mg and GDM risk (Poverall < 0.05 and Pnon-linear > 0.05). WQS analysis showed that the WQS index had a significant positive correlation with GDM (OR = 1.129, 95%CI: 1.023 ~ 1.247), with Fe (0.446) having greater weight. QGC analysis revealed a positive correlation between the combined action of five essential metal elements and GDM risk (OR = 1.161, 95%CI: 1.075 ~ 1.248), with Zn (0.454) and Fe (0.417) showing greater influence. In BKMR analysis, the combined effect of all essential metal elements on GDM showed an overall upward trend, with Fe (PIP = 0.772) having the most significant influence. No interaction between essential metal elements and GDM was found in this study.ConclusionHigher levels of Fe, Zn and Mg were positively correlated with GDM risk. The combined action of five essential metal elements was positively correlated with GDM, with Fe identified as playing the most significant role.